The Validity of the Sustainability Based Argument-Driven Inquiry to Improve Students’ Critical Thinking Skills - Nur Khoiri; Kukuh Sugandi; Joko Siswanto (Gagasan Pendidikan Indonesia, 2022)
The sustainability based argument-driven inquiry learning model is designed to improve students' critical thinking skills. The sustainability based argument-driven inquiry learning model as an effort in the education to prepare human resources ready to support the Sustainable Development Goals (SDGs). This study aimed to investigate the validity of the sustainability based argument-driven inquiry learning model to improve students' critical thinking skills. Validation is carried out with the stages of discussion, revision, and then filling out the validation sheet by experts. The results of the content obtained a score of 3.52 or included in the very valid category, and the construct validity obtained an average score of 3.67 or included in the very valid category. The validation results show that the lesson plan scored 72 out of 80 or 90% and is in the very valid category. The results of expert validation of the student worksheets obtained 55 out of 60 (92%) and were included in the very valid category. The results of expert validation of the assessment instrument show that the twelve questions are included in the valid category, and three questions are included in the very valid category.